2022
DOI: 10.3389/fnmol.2022.965756
|View full text |Cite
|
Sign up to set email alerts
|

Synapse-specific roles for microglia in development: New horizons in the prefrontal cortex

Abstract: Dysfunction of both microglia and circuitry in the medial prefrontal cortex (mPFC) have been implicated in numerous neuropsychiatric disorders, but how microglia affect mPFC development in health and disease is not well understood. mPFC circuits undergo a prolonged maturation after birth that is driven by molecular programs and activity-dependent processes. Though this extended development is crucial to acquire mature cognitive abilities, it likely renders mPFC circuitry more susceptible to disruption by genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 134 publications
0
7
0
Order By: Relevance
“…Conversely, microglial contact with dendritic spines could also increase the possibility of spine retraction by modifying the local extracellular matrix and reducing synaptic stability. Dendritic spine dynamics and synaptic AMPAR transport could be influenced by BDNF and TNFα, respectively, secreted by microglia, which perform their function of partially encapsulating synapses rather than engulfing them ( Blagburn-Blanco et al, 2022 ).…”
Section: Microglia Contribute To Neuroinflammation In Asd By Releasin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, microglial contact with dendritic spines could also increase the possibility of spine retraction by modifying the local extracellular matrix and reducing synaptic stability. Dendritic spine dynamics and synaptic AMPAR transport could be influenced by BDNF and TNFα, respectively, secreted by microglia, which perform their function of partially encapsulating synapses rather than engulfing them ( Blagburn-Blanco et al, 2022 ).…”
Section: Microglia Contribute To Neuroinflammation In Asd By Releasin...mentioning
confidence: 99%
“…More importantly, inhibitory neuronal function and synapses are modulated by specific ASD risk genes. For example, most of the behavioral features of RTT were reproducible when the risk MECP2 gene was deleted from all GABAergic interneurons ( Blagburn-Blanco et al, 2022 ).…”
Section: Microglia Contribute To Neuroinflammation In Asd By Releasin...mentioning
confidence: 99%
“…Little is known concerning the microglia’s influence on mPFC development and its function, such as social behavior [ 53 ]. As such, microglia are receiving significantly more attention in psychiatric research [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, microglia are receiving significantly more attention in psychiatric research [ 54 , 55 ]. In particular, understanding microglia’s role in the mPFC circuit formation is essential due to the critical implication of the mPFC in the pathobiology of neuropsychiatric disorders [ 53 , 56 58 ]. In this study, we first demonstrated that j-SI mice during p21–p35 had increased MG- Bdnf expression and reduced sociability, consistent with previous studies [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%